Design and development of 3D foot scanning rig - Muhammad Shahiruddin, Alias (2013)
This research is about design and development of 3D foot scanning rig. In 3D scanning industries, there are two mains applications that were used. There are David Laser Scanner and Kinect. For this research, it more focused into Kinect. Kinect is a motion sensing input device that can scan a subject and change to 3D image in Skannet’s software. Until todays, there is no rig that had made for kinect. The significant to develop kinect’s rig is to make the scanner easy to scan and can produce an accurate 3D image in the software. The objectives of this research are to design and fabricate the portable 3D foot scanning rig and to design a scanning rig that can get a constant radius when circulate a subject. In this research, there are two methodologies that are used. Firstly, design and fabricate the rig. The fabrication process included in this project is cutting of material, machining, drilling and finishing. The selection of the materials and the reasonbehind the selection are shown based on criteria predetermined. Second methodology is testing the rig. A kinect is attached to the rig and it circulates the subject. The scan result or the 3D image of the subject is shown in Skannect’s software. Modification process is done after the testing. From this rig, an excellent result had been produced. The rig can capture the subject’s image accurately and sharp in short time. It shows the rig can be used in future.